Bryozoan framework composition in the oddly shaped reefs from Abrolhos Bank, Brazil, southwestern Atlantic: taxonomy and ecology - Ramalho, Laís V.; Taylor, Paul D.; Moraes, Fernando Coreixas; Moura, Rodrigo; Amado-Filho, Gilberto M.; Bastos, Alex C. (Zootaxa, 2018)
Bryozoans are a key group of sessile invertebrates in some reef frameworks but are typically neglected in environmental monitoring programs. Abrolhos Bank (Brazil) is the largest reef complex in the South Atlantic Ocean, encompassing several reef landscapes over an area of 46,000 km2. A transition takes place across the shelf from mangroves to soft sediments, coastal shallow reefs to a volcanic archipelago – surrounded by fringing reefs – and unique mushroom-shaped biogenic structures, with mesophotic pinnacle reefs, rhodolith beds, sink-holes and shelf break deep environments. The taxonomic composition of the bryozoan fauna was studied in 11 core samples taken from shallow to mesophotic mid-shelf reefs (4–25 m deep) on Abrolhos Bank by divers using a submersible drill. Of the 20 bryozoan species sampled, 17 are new records for Abrolhos Bank and seven species are new to science: Crassimarginatella winstonae n. sp., Parasmittina distincta n. sp., Parasmittina abrolhosensis n. sp., Hemismittoidea asymmetrica n. sp., Stylopoma variabilis n. sp., Stylopoma hastata n. sp., and Plesiocleidochasma acuminata n. sp. (described by Ramalho, Taylor & Moraes). The most conspicuous species is Celleporaria atlantica. These results increase to 48 the total number of bryozoan species known in this region and reinforce the importance of this group as one of the main components apart from crustose coralline algae and corals of the reef framework-building community of Abrolhos Bank.